Psychometric Properties and Measurement Invariance of the English Version of the Satisfaction with Life Scale (SWLS) for Non-Native English Speakers - Giusy Danila Valenti; Palmira Faraci (MDPI AG, 2024)
This cross-cultural study seeks to (a) investigate the internal structure of the English version of the Satisfaction With Life Scale (SWLS) when administered to non-native English speakers (i.e., Asian individuals and (b) test for measurement invariance with its Italian counterpart). The whole sample comprises 338 participants, including 167 Asian international university students residing in the United States (50.3% females; Mage = 23.82, SD = 3.78) and 171 Italian university students living in Italy (69.6% females; Mage = 22.38, SD = 4.24). The dimensionality of the scale is assessed through confirmatory factor analysis (CFA), and multi-group confirmatory factor analysis (MG-CFA) is employed to examine measurement invariance. The results confirm the one-dimensionality of the SWLS [χ2 = 9.815; df = 5; CFI = 0.989; TLI = 0.977; SRMR = 0.027]. Furthermore, achieving full strict invariance indicates that the SWLS items exhibit similar structures across both samples. The scale shows satisfactory internal reliability (α = 0.863, ω = 0.866). Overall, this study supports the cross-validity of the English version of the SWLS and underscores its robustness and suitability for assessing life satisfaction among non-native English speakers.